Examining the “Invisible”: How are Published Translations Reviewed in the United Kingdom and France? - Gray, Martyn (Mémoires du livre / Studies in Book Culture, 2017)
In his 1995 seminal work, The Translator’s Invisibility, Lawrence Venuti examines the impact of how translations are reviewed on the visibility of the translator. The American scholar contends that a fluent translation approach, which ultimately makes the work of the translator “invisible” to the final reader, is the main criterion by which translations are read and assessed by reviewers; any deviations from such fluent discourse are thus dismissed as inadequate. The present research will draw upon a corpus of British and French reviews collected from two broadsheet supplements in each country to analyze the extent to which the media’s reviews of published translations continue to reinforce—or indeed challenge—the notion of translators’ invisibility. The research will demonstrate that, whilst fluency and transparency are still revered by a large number of reviewers, especially in the UK, the reviews in this corpus show a remarkable degree of openness towards diverse translation approaches.